2019
DOI: 10.1186/s12933-019-0865-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular organ damage in type 2 diabetes mellitus: the role of lipids and inflammation

Abstract: Background The relationship between dyslipidemia, inflammation and CV organ damage in type 2 diabetes mellitus (T2DM) is complex. Insulin resistance and inflammatory cytokines interleukins (ILs) increase plasma triglycerides (TG). ILs also up-regulate expression of matrix-metalloproteinases (MMPs) that, together with TG, decrease high density lipoprotein cholesterol (HDL) levels. High TG, low HDL, increased ILs and MMPs trigger structural and functional changes in different parts of cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Although the exact mechanisms underlying the relationship of the TyG index with arterial stiffness is unclear, it may be linked to IR. IR is associated with hyperinsulinaemia, hyperglycaemia, dyslipidemia, hypertension and a proin ammatory state, as well as the effect of perturbed insulin signaling at the level of the intimal cells (endothelial cells, vascular smooth muscle cells, and macrophages), all of which predispose to arterial stiffness [13,[35][36][37][38]. In our study, men showed larger regression coe cients and odds ratios of the TyG index in relation with increased arterial stiffness than women.…”
Section: Discussionmentioning
confidence: 46%
“…Although the exact mechanisms underlying the relationship of the TyG index with arterial stiffness is unclear, it may be linked to IR. IR is associated with hyperinsulinaemia, hyperglycaemia, dyslipidemia, hypertension and a proin ammatory state, as well as the effect of perturbed insulin signaling at the level of the intimal cells (endothelial cells, vascular smooth muscle cells, and macrophages), all of which predispose to arterial stiffness [13,[35][36][37][38]. In our study, men showed larger regression coe cients and odds ratios of the TyG index in relation with increased arterial stiffness than women.…”
Section: Discussionmentioning
confidence: 46%
“…Furthermore, matrix metalloproteinases are zinc-binding proteinases that degrade components of the extracellular matrix and whose production is upregulated notably by hyperglycaemia, pro-inflammatory mediators and reactive oxygen species [150]. Matrix metalloproteinase levels are associated with cardiovascular disease development and all-cause mortality in T1DM [151][152][153], and with cardiovascular organ damage in T2DM [154]. In diabetes, they increase inflammation, endothelial dysfunction, vascular remodelling and thrombus formation [155,156].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…The results from previous studies have shown that increased circulating GDF15 levels were closely associated with the development and progression of various cardiovascular diseases (including myocardial ischaemia/reperfusion, heart failure, atherosclerosis, and acute coronary syndrome), and were shown to be a strong and independent predictor of mortality and disease progression in patients with atherosclerosis and coronary artery disease [5][6][7][8][9][10][31][32][33][34][35][36]. In diabetic patients, higher levels of lipids and chronic inflammation may directly damage the cardiovascular system [37]. As expected, circulating GDF15 levels have also been shown to help identify and predict cardiovascular disease risk in patients with diabetes [16,38,39].…”
Section: Discussionmentioning
confidence: 99%